Structural Evolution of α-Fe2O3(0001) Surfaces Under Reduction Conditions Monitored by Infrared Spectroscopy - Schöttner, Ludger; Nefedov, Alexei; Yang, Chengwu; Heissler, Stefan; Wang, Yuemin; Wöll, Christof (Frontiers in Chemistry, 2019)
The precise determination of the surface structure of iron oxides (hematite and magnetite) is a vital prerequisite to understand their unique chemical and physical properties under different conditions. Here, the atomic structure evolution of the hematite (0001) surface under reducing conditions was tracked by polarization-resolved infrared reflection absorption spectroscopy (IRRAS) using CO as a probe molecule. The frequency and intensity of the CO stretch vibration is extremely sensitive to the electronic properties and coordination environments of surface iron cations. Our comprehensive IRRAS results provide direct evidence that the monocrystalline, stoichiometric α-Fe2O3(0001) surface is single Fe-terminated. The initial reduction induced by annealing at elevated temperatures produces surface oxygen vacancies, where the excess electrons are localized at adjacent subsurface iron ions (five-fold coordinated). A massive surface restructuring occurs upon further reduction by exposing to atomic hydrogen followed by Ar+-sputtering and annealing under oxygen poor conditions. The restructured surface is identified as a Fe3O4(111)/Fe1-xO(111)-biphase exposing both, Fe3+ and Fe2+ surface species. Here the well-defined surface domains of Fe3O4(111) exhibit a Feoct2-termination, while the reduced Fe1-xO(111) is Fe2+(oct)-terminated. These findings are supported by reference IRRAS data acquired for CO adsorption on magnetite (111) and (100) monocrystalline surfaces.